Pobreza e programas de transferência de renda: concepções e significados - Araújo, Cleonice Correia (2007)
This study presents the outcome of a theoretical and empirical research. The main subject is the poverty and its different conceptions and dimensions. The Programa Bolsa Família is its empirical reference. It is a program of income transfer to poor families being the main strategy to face poverty in Brazil nowadays. The research sought to apprehend the constitutive components of the poverty seen as a social construction from the action of the different social subjects related with the Program: formulators, practitioners, stressing the "beneficiary" point of view. The study reflects about the different explanatory approaches of the poverty, his constitution in the Brazilian thought, seeking to establish a relation with the thought of the subjects of that research. The objective is to find out the conceptions and the present meanings in the relation between the Programa Bolsa Família and the poverty.